The Multispecialistic da Vinci European BioBank. (18th November 2014) - Marcon, Giordana; Nincheri, Paola
The da Vinci European BioBank (daVEB) is a research infrastructure established in 2009 in the Scientific Campus of the University of Florence (Sesto Fiorentino, Italy) belonging to the non-profit foundation FiorGen, which promotes studies aimed at exploiting knowledge on human health. Since 2011, daVEB is ISO9001 certified for collection, storage and distribution of biological samples and the associated data for scientific research. The biobank is currently storing about 9.000 biospecimens (serum, plasma, white cells, tissue, DNA, cells and urine) collected according to specific informed consents by Research Units from healthy donors and patients affected by different diseases - cardiovascular diseases, melanoma, breast carcinoma, non-Hodgkin's lymphoma, cancer in geriatric patients, Krabbe syndrome, rare skin diseases; the biomaterial is available for new research projects.